Study the depiction of race and identity in Native American literature, focusing on authors like Sherman Alexie, Louise Erdrich, and Leslie Marmon Silko. - Dr. Anuma, Navita (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
First, we present a historically sensitive analysis of the ethnicities that dominated the nation's racial fantasy, noting how distinct ethnic groups were considered to be biologically, geographically, or socially connected. Second, we examine the descriptive phrases most associated with specific ethnicities throughout time to follow the shifting discursive landscapes surrounding specific racial groups. A brief introduction to Native American literature will be given at the opening. Then the meaning of the terms 'Native American' and 'Native American Literature', as well as the genesis and evolution of Native American literatures, must be investigated. Many renowned Native Americans have written poetry and prose.From antiquity till the late nineteenth century, their literature was an unwritten and anonymous oral tradition. Much later, anthropologists and linguists attempted to turn the nameless tradition into written literature that captured the spirit of the original. Thus, Native Americans are now composing poems and prose novels that carry on the creative activity that dates back to its ancient origins. Language was a marvelous thing to Native Americans. Taking a historical approach, the paper will first discuss the birth of Native American authors through the production of protest literature, autobiographies, and ethno histories in response to white American society's attempts to eliminate Native cultures.Thus, Native American written literature might be viewed as a unifying element for the various tribes, allowing Indians to forge a common indigenous identity in the face of European dominance in society. In this paper, we will discuss. Examine the representation of race and identity in Native American literature, with a focus on authors such as Sherman Alexie, Louise Erdrich, and Leslie Marmon Silko.